The epidemiology of bovine viral diarrhea virus in lowand middle-income countries: A systematic review and meta-analysis - Zirra-Shallangwa, B.; González Gordon, L.; Hernandez-Castro, L.E.; Cook, Elizabeth A.J.; Bronsvoort, B.M. de C.; Kelly, Robert F. (Frontiers Media, 2022)
Introduction: Bovine viral diarrhea virus (BVDV) causes reproductive inefficiencies and negatively impacts the economy of low- and middle-income countries (LMICs). It is characterized by a combination of syndromes that result in poor production performance and calf morbidity and mortality. BVDV control is possible by introduction of biosecurity measures, test-and-cull, and vaccination programs as accomplished in high-income countries. Knowledge of BVDV epidemiology is limited in many LMICs, which hinders implementation of effective control programs. We carried out a systematic review and meta-analysis to estimate the burden of BVDV, identify risk factors related to its occurrence, and health and economic impacts on production systems.